Potential of Energy Municipal Solid Waste (MSW) to Become Refuse Derived Fuel (RDF) in Bali Province, Indonesia - Suryawan, I Wayan Koko; Wijaya, I Made Wahyu; Sari, Novi Kartika; Septiariva, Iva Yenis; Zahra, Nurulbaiti Listyendah (Universitas Negeri Semarang, 2021)
The generation of municipal solid waste (MSW) in Bali has various environmental impacts. One of the updates on sustainable waste processing is the RDF treatment plant processing. Before carrying out the processing, MSW characterization is needed because each region has a diverse composition. The processing of MSW into RDF provides benefits for achieving MSW reduction targets, renewable energy use, and the reduction of greenhouse gas (GHG) emissions. For this reason, this study was conducted to determine the potential of MSW in Bali as an alternative to renewable fuel and its potential to reduce GHG. MSW's potential calorific value as a raw material for RDF in Bali can reach 9.58 - 17.71 MJ/kg. The implementation of processing waste into RDF in pellets has shown a calorific value of Â± 3904 - 4945 kkcal/kg. Implementing MSW processing into RDF in Bali can reduce GHG by 178 - 330 times compared to open dumping.